An evaluation of sulfidisation in the flotation recovery of heavily oxidised sulfide minerals : with particular reference to oxidised Merensky ores - Newell, Andrew James Haigh (Department of Chemical Engineering, 2014)
Includes bibiographical references (p. 165-180).